Towards cryogenic neutron crystallography on the reduced form of [NiFe]‐hydrogenase. Issue 10 (8th October 2020) - Hiromoto, Takeshi; Nishikawa, Koji; Inoue, Seiya; Matsuura, Hiroaki; Hirano, Yu; Kurihara, Kazuo; Kusaka, Katsuhiro; Cuneo, Matthew; Coates, Leighton; Tamada, Taro; Higuchi, Yoshiki
Abstract : Large crystals for neutron diffraction experiments were cooled anaerobically by two methods, cooling in a cold gas stream and plunge‐cooling into liquid nitrogen, and their respective effects on crystal quality were compared. Gas‐stream cooling was sufficient to suppress the increase in mosaicity over the entire crystal, leading to success in the first data collection for a membrane‐bound hydrogenase from Desulfovibrio vulgaris in its active reduced form. Abstract : A membrane‐bound hydrogenase from Desulfovibrio vulgaris Miyazaki F is a metalloenzyme that contains a binuclear Ni–Fe complex in its active site and mainly catalyzes the oxidation of molecular hydrogen to generate a proton gradient in the bacterium. The active‐site Ni–Fe complex of the aerobically purified enzyme shows its inactive oxidized form, which can be reactivated through reduction by hydrogen. Here, in order to understand how the oxidized form is reactivated by hydrogen and further to directly evaluate the bridging of a hydride ligand in the reduced form of the Ni–Fe complex, a neutron structure determination was undertaken on single crystals grown in a hydrogen atmosphere. Cryogenic crystallography is being introduced into the neutron diffraction research field as it enables the trapping of short‐lived intermediates and the collection of diffraction data to higher resolution. To optimize the cooling of large crystals under anaerobic conditions, the effects on crystal quality were evaluated by X‐rays using two typical methods, the use of a cold nitrogen‐gas stream and plunge‐cooling into liquid nitrogen, and the former was found to be more effective in cooling the crystals uniformly than the latter. Neutron diffraction data for the reactivated enzyme were collected at the Japan Photon Accelerator Research Complex under cryogenic conditions, where the crystal diffracted to a resolution of 2.0 Å. A neutron diffraction experiment on the reduced form was carried out at Oak Ridge National Laboratory under cryogenic conditions and showed diffraction peaks to a resolution of 2.4 Å.